PELAKSANAAN JUAL BELI TANAH ANTARA NINIK MAMAK BUKIK LIMBUKU DENGAN ANAK NAGARI KAPEH PANJI KECAMATAN BUNUHAMPU KAB.AGAM SUMATERABARAT MENURUT HUKUM ADAT - Putri Nilam Sari; Evi Deliana; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The customary land of the people in the MinangKabau Customary Law community is a treasure that is always at stake, because the authority of a people lies from some of the customary land owned by the people they own. The land functions for the interests and welfare of members of the hereditary generation, basically the customary communal land of the people may not be traded or diverted for granted and may only be mortgaged but must meet one of the requirements namely: maik tabujua in the middle of a house, a drainage house, drainage gadang alun balaki, summoning the tarandam trunk. At present it is permissible to sell customary land in accordance with these conditions. In connection with the foregoing, problems arise: How is the sale and purchase of land between the ninik mamak Pilubang and the children of Nagari Kapeh Panji, BunuhAmpu Subdistrict, Agam Regency according to customary law, What are the legal consequences of buying and selling land between the ninik mamak Pilubang and the child of Nagari Kapeh Panji Subdistrict, Bunakam District, Agam Regency according to customary law.In writing this thesis, the author uses a sociological juridical approach method by analyzing various regulations that apply to the customary law community in Nagari Pilubang, as well as analyzing laws that are seen as community behavior that is patterned in the lives of people who always interact and relate to social aspects. . The results of research and discussion can be seen that, Nagari Pilubang ulayat land still exists, but as a result of the shift in customary law at this time the initial ulayat land of the people may not be traded, but can be sold by their people, in selling ulayat land there must be procedures and processes that must be passed, starting from the internal process of the clan, such as having to get the approval of all members of the clan to the process of filing, customary land is sold by their people due to several factors, namely factors of economic importance, economic speculation and also harys for the interests and welfare of the community folk.Keywords: Implementation Buying and selling, Ulayat Land